1978
DOI: 10.1172/jci109154
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic and Gastric Somatostatin Release in Response to Intragastric and Intraduodenal Nutrients and HCl in the Dog

Abstract: A B S T R A C T The effects of the instillation of glucose, fat, casein hydrolysate, and HCI into the gastrointestinal tract upon plasma levels of somatostatin-like immunoreactivity (SLI) in the venous effluent of the pancreas, fundus and antrum of the stomach, and in the inferior vena cava (IVC) were determined in normal laparotomized dogs. Fasting SLI levels in the effluent plasma from these sites were significantly greater than IVC levels. The intragastric administration of glucose elicited a prompt and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
74
0
6

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(86 citation statements)
references
References 32 publications
6
74
0
6
Order By: Relevance
“…SLI output from the right lobe of the pancreas increased by 684±227 pg/min and that from the gastrointestinal tract increased by 23,911±3,197 pg/ min, again suggesting that the pancreas was a minor source of circulating SLI even when the D cells were stimulated. We conclude that the measurement of arterial-venous SLI concentrations, in the absence of measurements of Introduction Somatostatin-like immunoreactivity (SLI)' is present in high concentrations in the D cells of the pancreatic islet (1,2) and in the venous effluent of the pancreas (3)(4)(5). These observations have led to the assumption (5-9) that the pancreas makes a significant contribution to the SLI circulating in peripheral and portal venous plasma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SLI output from the right lobe of the pancreas increased by 684±227 pg/min and that from the gastrointestinal tract increased by 23,911±3,197 pg/ min, again suggesting that the pancreas was a minor source of circulating SLI even when the D cells were stimulated. We conclude that the measurement of arterial-venous SLI concentrations, in the absence of measurements of Introduction Somatostatin-like immunoreactivity (SLI)' is present in high concentrations in the D cells of the pancreatic islet (1,2) and in the venous effluent of the pancreas (3)(4)(5). These observations have led to the assumption (5-9) that the pancreas makes a significant contribution to the SLI circulating in peripheral and portal venous plasma.…”
mentioning
confidence: 99%
“…However, the amount of somatostatin actually released from the pancreas appears to be relatively small, at least in vitro (10,11), and the very short half-time of somatostatin in vivo (12)(13)(14) suggests that a large output of somatostatin would be necessary to appreciably influence the arterial or portal venous level of SLI. Furthermore, other evidence (1,3,4,15,16) suggests that the gastrointestinal tract contributes significantly to circulating SLI. Therefore, we sought to determine whether or not the pancreas is a major source of the changes of SLI in arterial and portal venous plasma.…”
mentioning
confidence: 99%
“…Stimulation of somatostatin release is associated with increased secretion into the venous outflow, and there may also be detectable changes in the systemic circulation (Schusdziarra, Harris, Conlon, Arimura & Unger, 1978;Chiba et al 1980;Saffouri et al 1980). Even so, the primary action of somatostatin is thought to be local, or paracrine, and not hormonal (Larsson, Goltermann, De Magistris, Rehfeld & Schwartz, 1979).…”
Section: Control Of Somatostatin Synthesismentioning
confidence: 99%
“…The effect of an increase in Ca++ from the control level of 1.5 (6)(7)(8), and in vivo and in vitro studies have demonstrated that the somatostatin is released in response to various physiological and pharmacological stimuli (9)(10)(11)(12). These findings have contributed to the idea that somatostatin acts as a physiological paracrine mediator.…”
mentioning
confidence: 97%